ADMINISTRASI DAN LEGALITAS USAHA UMKM PADA KELOMPOK JAMUR TIRAM SEJAHTERA - Elni Sumiarti; Yosi Suryani; Sarmiadi; Dan Iwadiah, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
UMKM must know and understand administration because effective administration can improve the way they do business, especially with regard to financial reporting. In addition, UMKM must operate legally so that consumers can consume their products without hesitation because they know that they have been checked by BPOM. The Kelompok Jamur Tiram Sejahtera, one of the UMKM in Limau Manis, which has been operating for approximately two years, but does not have adequate administration, accurate financial reporting, and clear legal status, which will hamper business growth, especially in terms of marketing. The Devotion Team tries to motivate the group to prepare financial reports and help manage business legality. This is one of the activities to increase promotion and improve administration, especially in terms of finance, as well as systems and methods to manage business legality. The activities carried out are by conducting training and providing examples of how to prepare financial reports. The purpose of this activity is so that UMKM actors can handle business licensing, PIRT, being registered with BPOM, and simple administrative tasks so that the PIRT number appears. The Kelompok Jamur Tiram Sejahtera can use this information in their marketing efforts to help consumers feel confident in purchasing their products.